CORPORATE CRIME IN INDONESIAN ENVIRONMENTAL LEGAL POLICY: A GOVERNANCE PERSPECTIVE - Salim, Achmad Mujadid; Hikam, Reza Maulana (Jurnal Kebijakan Pemerintahan, 2024)
Abstract Corporate crime has been a concern in the development of criminal law for a long time and the Indonesian society has concern regarding the implementation of the legal system. This research paper examines corporate crime in the context of environmental law in Indonesia, providing a legal-philosophical analysis of the responsibilities of corporations and the implications for victims of environmental crimes. The study highlights the philosophical underpinnings of the rule of law in Indonesia, emphasizing the collective will of the people and the limitations of state power. It investigates the intersection of criminal law, corporate law, and environmental law, particularly focusing on the Lapindo Mud Case in Sidoarjo, East Java as a significant example of corporate environmental malpractice. The paper discusses the principles of legality in criminal law, the complexities of corporate criminal liability, and the evolving definitions of victims in environmental crimes. It argues that environmental crimes perpetrated by corporations not only harm individuals but also have broader impacts on communities, ecosystems, and the state. Ultimately, the research calls for a more robust legal framework to hold corporations accountable and protect victims, advocating for an integrated approach that recognizes the rights of both individuals and the environment. Keywords: Corporate Crime, Environmental Legal Policy, Indonesia, Legal Philosophy